ڈیرہ اسماعیل خان: تہذیبی و ثقافتی پس منظر (Al-Qamar, 2023)
Dera Ismail Khan is a city with a diverse temperament in terms of geography and culture.  It also has fields, mountains, deserts, rivers, and trees such as mango, Dates, etc. Similarly, Pashto, Seraiki, Punjabi culture have come into it and taken a new form. Because of this diverse culture, it is also colorful in its literature.  The style of clothing, food, marriage, death here makes it different from the meeting around you. This diversity of culture is the new galaxy of poetry and literature, when expressing emotions and thoughts here.
Keywords: Dera Ismail Khan; Geographical and Cultural; Pashto; Seraiki; Diverse Culture; Poetry and Literature